2017
DOI: 10.1073/pnas.1701836114
|View full text |Cite
|
Sign up to set email alerts
|

Mouse model of Epstein–Barr virus LMP1- and LMP2A-driven germinal center B-cell lymphoproliferative disease

Abstract: Epstein-Barr virus (EBV) is a major cause of immunosuppression-related B-cell lymphomas and Hodgkin lymphoma (HL). In these malignancies, EBV latent membrane protein 1 (LMP1) and LMP2A provide infected B cells with surrogate CD40 and B-cell receptor growth and survival signals. To gain insights into their synergistic in vivo roles in germinal center (GC) B cells, from which most EBV-driven lymphomas arise, we generated a mouse model with conditional GC B-cell LMP1 and LMP2A coexpression. LMP1 and LMP2A had lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 52 publications
0
49
0
Order By: Relevance
“…The knockout of key pathway components promises to reveal why LMP1-induced canonical and noncanonical NF-B are each critical for LCL growth and survival, when they first become critical dependency factors, and how the crosstalk between LMP1-activated NF-B, MAPK, PI3 kinase, and interferon regulatory factor pathways sculpts target gene regulation. Similarly, LMP1 and LMP2A are typically coexpressed and colocalize in cell membranes, yet mechanisms by which they synergistically regulate a wide range of GC B-cell target genes are yet to be identified (69).…”
Section: Future Directionsmentioning
confidence: 99%
“…The knockout of key pathway components promises to reveal why LMP1-induced canonical and noncanonical NF-B are each critical for LCL growth and survival, when they first become critical dependency factors, and how the crosstalk between LMP1-activated NF-B, MAPK, PI3 kinase, and interferon regulatory factor pathways sculpts target gene regulation. Similarly, LMP1 and LMP2A are typically coexpressed and colocalize in cell membranes, yet mechanisms by which they synergistically regulate a wide range of GC B-cell target genes are yet to be identified (69).…”
Section: Future Directionsmentioning
confidence: 99%
“…Interestingly, recent transgenic mouse studies provide evidence that EBV proteins can also inhibit GC biology, particularly in the context of T cell defects. Expression of LMP1 and LMP2A in GC B lymphocytes under control of the AID promoter produced fatal lymphoproliferations only when both T and NK cells were depleted in the same animals [28]. In this model, which mimics EBV-HIV co-infection, there was a significant increase in the IgM plasmablast response, indicating that completion of the normal GC reaction was inhibited.…”
Section: Influence Of Ebv As a Co-pathogen In Pelmentioning
confidence: 99%
“…Different from the application of humanized mouse model, a recent study reported establishment of a transgenic mouse model with conditional LMP1/2A coexpression in germinal center (GC) B cells [95]. In this mouse model, LMP1/2A showed very limited function in immunocompetent mice, while they promote B-cell lymphoproliferative diseases in the context of T-cell or NK-cell deficiency [95].…”
Section: 3 Molecular Biology Of Ebv-mediated B-cell Lymphomasmentioning
confidence: 99%
“…In this mouse model, LMP1/2A showed very limited function in immunocompetent mice, while they promote B-cell lymphoproliferative diseases in the context of T-cell or NK-cell deficiency [95]. …”
Section: 3 Molecular Biology Of Ebv-mediated B-cell Lymphomasmentioning
confidence: 99%